2015
DOI: 10.1589/jpts.27.1961
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and responsiveness of algometry for measuring pressure pain threshold in patients with knee osteoarthritis

Abstract: [Purpose] This study aimed to establish the intrarater reliability and responsiveness of a clinically available algometer in patients with knee osteoarthritis as well as to determine the minimum-detectable-change and standard error of measurement of testing to facilitate clinical interpretation of temporal changes. [Subjects] Seventy-three patients with knee osteoarthritis were included. [Methods] Pressure pain threshold measured by algometry was evaluated 3 times at 2-min intervals over 2 clinically relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 46 publications
0
75
0
2
Order By: Relevance
“…The number of trials ranged from 2 to 4 for PPT measurements, except for one study that conducted only 1 trial and one study that did not report the number of trials . For studies that conducted more than 1 trial, only 4 studies reported rest periods; these ranged from 20 seconds to 1 minute between trials …”
Section: Resultsmentioning
confidence: 99%
“…The number of trials ranged from 2 to 4 for PPT measurements, except for one study that conducted only 1 trial and one study that did not report the number of trials . For studies that conducted more than 1 trial, only 4 studies reported rest periods; these ranged from 20 seconds to 1 minute between trials …”
Section: Resultsmentioning
confidence: 99%
“…Keywords: Acupuncture; Pain; Pressure algometry; Rheumatoid arthritis; Turning point syndrome Citation: Seca S, Miranda D, Patrício M, Correia R, Kirch S, et al (2017) Although self reported pain intensity is important, it is a composition of the physiological and psychological features of the patient and their health problem that is further mediated by social aspects, which can make it difficult to interpret the responses [17].…”
Section: Discussionmentioning
confidence: 99%
“…Although self reported pain intensity is important, it is a composition of the physiological and psychological features of the patient and their health problem that is further mediated by social aspects, which can make it difficult to interpret the responses [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of training method has been shown to have good reliability . The minimal clinically important difference was considered to be 1.62 kg/cm 2 .…”
Section: Methodsmentioning
confidence: 99%